PENGARUH FASILITAS BELAJAR TERHADAP MOTIVASI BELAJAR SISWA KELAS X SMA SANTO FRANSISKUS ASISI PONTIANAK - Lirung, Raymondus; Aminuyati, Aminuyati; Khosma, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis entitled "The influence of learning facilities on the motivation of students of class X in economics at SMA Santo Fransiskus Asisi Pontianak" common problem in this research is "Is there any influence of learning facilities to the motivation of learning of class X students in economics subject at SMA Santo Francis Asisi Pontianak ". The variables in this study are learning facilities and students' motivation. The method used in this research is descriptive method in the form of relationship studies. The result showed that there is influence between the independent variable (X) to the dependent variable (Y) shown in Y = 14.290 + 0.721X which means the constant value is 14.290 ie if learning facility (X) is 0 (zero), then the learning motivation Y) worth 14,290. The correlation coefficient value of learning facility variables (X) of 0.721. means the increase of learning facilities of 1, then the learning motivation will increase by 0.721 and test t test hypothesis t count> t table, because the value of t count> t table is 12.044> 1.981, then Ha accepted and Ho rejected or "motivation to learn the grade X students in SMA St. Francis Pontianak Asisiâ€.Keywords: Learning facilities, learning motivation